PERFORMA RUMPUT LAUT, Gracilaria gigas, PADA SISTIM BUDIDAYA LAUT DAN TAMBAK - Farah Diana (JURNAL PERIKANAN TROPIS, 2016)
Gracilaria gigas is one of seaweed species the from red algae type (Rhodophyceae) producsy agarofit, G. gigas have the high fiber and good for health. The research aims to analyze the performance of production, yield and quality of G. gigas seaweed cultivated in the sea and in the ponds. The cultivation of G. gigas in ponds was held in Sekotong, west Lombok by broadcast method in 1500 m2planting area. While cultivation in the sea was held in  Gerupuk Bay, Central Lombok by Long-line method the 1250 m2. Parameters measured include the performance of seaweed , and water quality . While water quality parameters measured are temperature , salinity , pH , NO3 - N , NO2 - N , NH3 - N , PO4 - P and brightness were taken on days 0 , 10 , 20 and 30. Based on the research results obtained performance parameters seaweed cultivation consisting of productivity of cultivation, the total number thalus ( JT ) , the number of thalus secondary ( JTS ) , the number of thalus tertiary ( AAC) and the index of branching ( IP ) from seaweed cultivated on two habitats different , namely marine and pond. The average productivity of Gracilaria . gigas were in cultivation in the sea that is 12.72 % , whereas in ponds with an average of 4.00% . Total thalus on Gracilaria gigas cultured in ponds is high ( 86.56 ) than in the sea ( 80.40 ). Branching index is closely related to the availability of nutrients and nutrient in the formation of new cells , in which the N content in ponds is higher than in the sea . In addition , the number of tertiary thalus